2022
DOI: 10.2147/ijn.s372343
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo (Albino Mice) and in-vitro Assimilation and Toxicity of Zinc Oxide Nanoparticles in Food Materials

Abstract: Purpose Recent advances in nanotechnology have given rise to the potential utilization of nanoparticles as food, nano-medicine/biomedicines. Patient The study aimed to investigate the effects of nano-zinc oxide (nano-zinc) on the bio-assimilation of mineral (Zn) in mice, aged 3–6 weeks. Methods ZnO nanoparticles were added to the basal diet as a supplement at amounts of 0.07, 0.14 and 0.21 mg/kg. The synthesized material was characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 47 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…When the FT-IR spectrum of the P(NVC-co-BZMA) copolymer shown in Figure 2 was examined, the main peaks characterizing the copolymer were found as follows: peaks of aromatic C-H stretching vibrations between 2980-3048 cm -1 , peaks of aliphatic C-H stretching vibrations between 2840 and 2980 cm -1 , peak of ester carbonyl at 1723 cm -1 , peak of C=C stretching vibrations in the aromatic ring at 1450 cm -1 , peak of vinylidene at 1330 cm -1 , peaks of the (-C=O)-O-C group between 1156 and 1240 cm -1 , and peaks of C-H stretching vibrations of monosubstituted benzene at 695 cm -1 . The peak at 837 cm -1 , due to the nano ZnO, was below the peak at the same location in the composite structure and caused this peak to broaden (Haldar et al, 2011;Bashir et al, 2022).…”
Section: Ft-ir Spectroscopymentioning
confidence: 98%
“…When the FT-IR spectrum of the P(NVC-co-BZMA) copolymer shown in Figure 2 was examined, the main peaks characterizing the copolymer were found as follows: peaks of aromatic C-H stretching vibrations between 2980-3048 cm -1 , peaks of aliphatic C-H stretching vibrations between 2840 and 2980 cm -1 , peak of ester carbonyl at 1723 cm -1 , peak of C=C stretching vibrations in the aromatic ring at 1450 cm -1 , peak of vinylidene at 1330 cm -1 , peaks of the (-C=O)-O-C group between 1156 and 1240 cm -1 , and peaks of C-H stretching vibrations of monosubstituted benzene at 695 cm -1 . The peak at 837 cm -1 , due to the nano ZnO, was below the peak at the same location in the composite structure and caused this peak to broaden (Haldar et al, 2011;Bashir et al, 2022).…”
Section: Ft-ir Spectroscopymentioning
confidence: 98%
“…Results showed that the group treated with small-sized nanoparticles, having a higher surface area, exhibited a greater reduction in tumor size compared to the group treated with large-sized nanoparticles. This suggests that surface area influences the therapeutic effectiveness of zinc oxide nanoparticles in lung cancer treatment [28]. Moreover, the surface area of ZnO NPs can be modified through various surface modification techniques, including surface functionalization and doping, which can alter their physicochemical properties and improve their performance in specific applications.…”
Section: Surface Areamentioning
confidence: 99%